FRAUD PELAPORAN KEUANGAN SEKTOR PUBLIK - Siti Sholihah; - Prasetyono (JAFFA, 2016)
The purpose of this study is to determine the forms of fraud that occured in public sector financial reporting. Based on the report ACFE (Association of Certified Fraud Examiner) in 2012, the financial reporting fraud cases lead to an average loss of $ 1 million. This study was included a qualitative study using interpretive paradigm. The informants are the staff who handle the reporting in public sector. Interviews were done by unstructure and informant didn’t know that they became informant in this research . The results of interviews indicate that public sector financial reporting fraud happens is misplaced account, negligence recognition grants/aid from the center goverment, accountability document manipulation, depreciation of assets disproportionate, estimates in determining the remaining inventory and estimated useful life of the asset.